Der Wille zum Nichts - Damir Barbarić (Phainomena)
The Will to Nothing --- The once vigorous and intense discussion of the problems gathered under the name of “nihilism” has recently noticeably lost its dynamism and productivity. The thesis of the present article is that the understanding of the essence of nihilism is only possible with sufficient insight into the metaphysical history of the West as it was authoritatively thought out and presented by Nietzsche. It is therefore necessary to rethink Nietzsche’s basic insights into the essence of nihilism in all forms of its appearance. In the main part of the paper, the meaning of the will to power as a central category of Nietzsche’s philosophy is discussed in detail, and, on this basis, it is shown that the basic definition of nihilism in Nietzsche is contained in his most principle statement that the will as such cannot cease to be a will, i.e. abandon and abolish itself, and that therefore it will rather will nothing than not will at all. From this it could possibly be concluded that a kind of positive nihilism, which Nietzsche announces as a Dionysian or divine way of thinking and living, should have as its starting point the relaxation and loosening of the will to power in contrast to its self-enhancement and empowerment.